A rare case of lamotrigine-induced acute interstitial nephritis. Issue 6 (1st January 2016) - Matta, Atul; Assalie, Nour Abou; Gupta, Rajib K.; Morales, Maria del Pilar; Conti, Ricardo
Abstract : Medications, especially non-steroidal anti-inflammatory drugs and antimicrobials, have been most commonly associated with acute interstitial nephritis (AIN); antiepileptic drugs (AEDs) are rarely known to cause AIN. This is a case of a 27-year-old male who was recently started on treatment with lamotrigine for bipolar disorder and was found to have rapidly progressive renal failure. Renal biopsy features were suggestive of AIN. Lamotrigine-induced AIN was suspected to be the most likely cause. Discontinuation of the drug and treatment with steroids resulted in complete renal recovery. Lamotrigine use has been recently gaining popularity, not only as an AED but also as a mood stabilizer. With the use of this drug becoming more popular, it is important to emphasize that – although rare – AIN is one of its potential complications.